The Meaning Of Qualisign Signs In Tere Liye's Novel Bumi And Its Implication For Literature Learning In Vocational Schools - B. Syukroni Baso; Johar Amir; Kembong Daeng (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
This research aims to analyze the meaning of qualisigns in the novel Bumi by Tere Liye and its implications for literature learning in vocational schools (SMK). The research method used is qualitative descriptive with semiotic analysis technique. The data used are quotations from the novel Bumi that contain qualisigns. The results show that qualisigns in the novel Bumi have various meanings, such as attentive, polite, angry, and others. These signs are presented by the author as a representation of the characters or situations presented in the novel. The quotations that become the focus of the study, namely "Dasar guru sok galak. Tidak tahu apa, tambah keriting saja rambutnya setiap kali dia marah-marah" and "Di dalam kardus berwarna pink, beralaskan talam lembut, ditutup kain sutra, hadiah ulang tahunku menunggu," contain qualisigns that have clear meanings. The implications of this research for literature learning in SMK are the importance of understanding literary semiotics as a theoretical foundation for understanding the meaning of signs in literary works. Literature learning in SMK should include an understanding of literary signs, both qualisigns and other signs, so that students can appreciate and understand literary works better